Inovasi dalam Pengembangan Bahan Ajar dan Media Pembelajaran Akhlaq - Idul Adha; Faridi Faridi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Akhlaq education plays an important role in shaping the character and personality of students. However, challenges in learning akhlaq such as limited relevant teaching materials and interesting learning media require innovative solutions. This article discusses strategies for developing teaching materials and learning media for akhlaq that are relevant to technological developments and social changes. This research uses literature study method and implementation analysis in selected schools. The results show that the use of digital media, project-based learning, and collaboration with parents and the community can improve the effectiveness of akhlaq learning.